Fabrication of Detonation Nanodiamonds Containing Silicon‐Vacancy Color Centers by High Temperature Annealing. Issue 19 (29th July 2021) - Shimazaki, Konosuke; Kawaguchi, Hiroki; Takashima, Hideaki; Segawa, Takuya Fabian; So, Frederick T.-K.; Terada, Daiki; Onoda, Shinobu; Ohshima, Takeshi; Shirakawa, Masahiro; Takeuchi, Shigeki
Abstract : Detonation nanodiamonds (DNDs) with sizes below 10 nm have attracted attention as single photon emitters with potential in many research fields from life sciences to quantum technologies. However, while nitrogen‐vacancy (NV) color centers are found in nanodiamonds directly after the detonation synthesis without the need for irradiation or annealing, silicon‐vacancy (SiV) color centers are not present in these pristine samples. Herein, SiV centers are created in DNDs by an annealing treatment up to 1100 °C in high vacuum. As silicon is not added, the precursor of the SiV centers must be pristine silicon impurities inside the nanodiamond lattice. A sharp emission line at the wavelength of 737 nm with a linewidth of 7.7 nm is observed in DNDs that are electron irradiated before annealing. This wavelength is consistent with the characteristic emission line of SiV centers and its linewidth is comparable with that in larger nanodiamonds created by chemical vapor deposition and subsequent milling. The average lifetime (0.4 ± 0.04 ns) of the fluorescence, which is in the range of reported lifetimes in nanodiamonds, also support that the observed emission peak are due to SiV centers in DNDs. Abstract : By an annealing treatment up to 1100 °C in high vacuum, silicon‐vacancy (SiV) color centers are created in detonation nanodiamonds (DNDs). A sharp emission line at the wavelength of 737 nm with a linewidth of 7.7 nm is observed in DNDs. This linewidth is comparable with that in high‐quality nanodiamonds created by chemical vapor deposition and subsequent milling.